Positive psychology for healthcare professionals a toolkit for improving wellbeing - MacFarlane, Jan; Carson, Jerome (Emerald Publishing, 2023)
Positive Psychology for Healthcare Professionals presents applied positive psychology specifically for health and care staff, showcasing eleven different interventions that have proven to be effective in improving wellbeing
Keywords: Positive psychology; Well-being; Medical personnel; Hospitals / Medical staff; Psychologie positive; Bien-être; Personnel médical; Hôpitaux / Personnel médical; comfort (sensation)